Stimulus-responsive vesicular polymer nano-integrators for drug and gene delivery - Mu X (Dove Medical Press, 2019)
Xin Mu,1,2 Shenglong Gan,1,2 Yao Wang,1,2 Hao Li,1,2 Guofu Zhou1,21Guangdong Provincial Key Laboratory of Optical Information Materials and Technology & Institute of Electronic Paper Displays, South China Academy of Advanced Optoelectronics, South China Normal University, Guangzhou 510006, People’s Republic of China; 2National Center for International Research on Green Optoelectronics, South China Normal University, Guangzhou 510006, People’s Republic of ChinaAbstract: Over the past two decades, nano-sized biosystems have increasingly been utilized to deliver various pharmaceutical agents to a specific region, organ or tissue for controllable precision therapy. Whether solid nanohydrogel, nanosphere, nanoparticle, nanosheet, micelles and lipoproteins, or “hollow” nanobubble, liposome, nanocapsule, and nanovesicle, all of them can exhibit outstanding loading and releasing capability as a drug vehicle – in particular polymeric nanovesicle, a microscopic hollow sphere that encloses a water core with a thin polymer membrane. Besides excellent stability, toughness and liposome-like compatibility, polymeric nanovesicles offer considerable scope for tailoring properties by changing their chemical structure, block lengths, stimulus-responsiveness and even conjugation with biomolecules. In this review, we summarize the latest advances in stimulus-responsive polymeric nanovesicles for biomedical applications. Different functionalized polymers are in development to construct more complex multiple responsive nanovesicles in delivery systems, medical imaging, biosensors and so on.Keywords: nanovesicle, stimulus-responsive, amphiphilic block copolymer, self-assembled, drug delivery